Strategies for property rates debt management: Practical interventions for debt recovery - Enwereji, Prince (Edelweiss Applied Science and Technology, 2025)
This study explored the strategies for property rates debt management and the practical interventions for debt recovery in South African local municipalities. The research objectives that guided this study include reviewing taxpayers’ behavioral theories that can facilitate payment compliance, examining the property rates payment guidelines and debt collection policies of local municipalities in South Africa, outlining practical debt collection measures to enhance payment compliance, and highlighting the best practices in property rates debt collection. The study adopted a qualitative research approach where a literature review was used as the only source of data collection. Findings revealed practical debt collection measures such as early intervention strategies, engagement of third-party agencies, and legal actions against defaulters. The study also draws insights from best practices in Canada and OECD countries and emphasized the role of technology, effective communication, and stringent enforcement in ensuring compliance. Recommendations for both municipalities and residents are provided, focusing on transparency, community participation, and equitable service provision. The findings from the study underline the necessity of a reciprocal relationship between municipalities and residents to foster a culture of compliance and financial sustainability.